PENANGANAN ANAK TERLANTAR MELALUI PANTI SOSIAL ASUHAN ANAK (PSAA) DI JAWA TENGAH - Hadi Karyono (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2014)
Childcare Institutions as the vanguard of the state in carrying out state duties as instructed dalamn Constitution of the Republic of Indonesia Year 1945 section 34 subsection (1) "The poor and neglected children maintained the State". Childcare Institutions have the task of guiding children abandoned in order to realize the right of the child or the child's needs are survival growth and development, protection and participation, so that children develop naturally. Lack of Childcare Institutions in capacity and funding appears to have the impression that there were not maintained waifstate. Population 4.5 million children displaced Indonesian Ministry of Social Affairs in data collection in 2012 is expected to continue to increase in line with social changes that occur continuously present. This study describe the handling problems of street children through PSAA is always expected but can not accommodate the number of children displaced existing reality. The method used in this study is empirical juridical using secondary data. Abandoned children is the duty and responsibility of the state , the provision of child care social institutions bin should be increased both capacity and quality, so that neglected children can be accommodated in the PSAA overall , not handed over to NGOs or thrown to the public.